2013
DOI: 10.1007/s10886-013-0289-9
|View full text |Cite
|
Sign up to set email alerts
|

Biotransfer, Bioaccumulation and Effects of Herbivore Dietary Co, Cu, Ni, and Zn on Growth and Development of the Insect Predator Podisus maculiventris (Say)

Abstract: Increased metal availability in the environment can be detrimental for the growth and development of all organisms in a food web. In part, this toxicity is due to biotransfer or bioaccumulation of metals between trophic levels. We evaluated the survival, growth, and development of a generalist Hemipteran predator (Podisus maculiventris) when fed herbivorous prey (Spodoptera exigua) reared on artificial diet amended with Cu, Zn, Ni, and Co. Predator nymphs were fed S. exigua larvae raised on diet amended with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Boyd and Wall (2001) found similar results suggesting that Ni could be passed from herbivorous to carnivorous insects. A laboratory study by Cheruiyot et al (2013), using caterpillars of Spodoptera exigua (Lepidoptera: Noctuidae) raised on metal-amended artificial diet and then fed to the predator Podisus maculiventris (Hemiptera: Pentatomidae), found that Cu and Zn were bioaccumulated whereas Co and Ni were not. These studies show that metals may be transferred between invertebrates; however, more research should focus on such transfers, as metals may continue to pose a risk to invertebrates by moving through food webs well after point sources of metal pollution have been closed (Babin-Fenske and Anand 2010, 2011).…”
Section: Invertebratesmentioning
confidence: 99%
“…Boyd and Wall (2001) found similar results suggesting that Ni could be passed from herbivorous to carnivorous insects. A laboratory study by Cheruiyot et al (2013), using caterpillars of Spodoptera exigua (Lepidoptera: Noctuidae) raised on metal-amended artificial diet and then fed to the predator Podisus maculiventris (Hemiptera: Pentatomidae), found that Cu and Zn were bioaccumulated whereas Co and Ni were not. These studies show that metals may be transferred between invertebrates; however, more research should focus on such transfers, as metals may continue to pose a risk to invertebrates by moving through food webs well after point sources of metal pollution have been closed (Babin-Fenske and Anand 2010, 2011).…”
Section: Invertebratesmentioning
confidence: 99%
“…Boyd and Moar [ 138 ] reported that tissues of the Ni hyperaccumulator S. polygaloides was toxic to S. exigua when plants hyperaccumulated Ni. Cheruiyot et al [ 139 ] used artificial diets to determine lethal and sub lethal concentrations of four metals (Co, Cu, Ni and Zn) to S. exigua . Another experiment explored the toxicity of four metals hyperaccumulated by plants (Cd, Ni, Pb and Zn) and searched if metal combinations might broaden the defensive effectiveness of metals in S. polygaloides [ 127 ].…”
Section: Influence Of Heavy Metals In the Response Of Plants To Bimentioning
confidence: 99%
“…HM exposure can alter natural enemy development time, adult weight, longevity and starvation tolerance. HM contaminated prey or water sources have been revealed to lengthen development time [44][45][46][47][48]. For example, when feeding on hosts contaminated with copper (Cu), Nasonia vitripennis (Hymenoptera: Pteromalidae), exhibited lengthened developmental time and reduced emergence of adult parasitoids from the pupal stage [45].…”
Section: Development Time and Body Sizementioning
confidence: 99%